Pendampingan Pembentukan Posyandu Lansia melalui Penguatan Kapasitas Kader - Karera, Anggita Dian (Universitas Muhammadiyah Mataram, 2026)
Abstract: The increasing elderly population requires community-based health services capable of providing promotive and preventive monitoring. The target community had no elderly integrated health post and local health volunteers lacked basic health examination skills, resulting in suboptimal elderly care. This community service aimed to facilitate the establishment of an elderly integrated health post through capacity strengthening of community health volunteers. The program was implemented using a community service learning approach consisting of coordination, organizational formation, training on basic health examination, elderly exercise training, and mentoring of the first elderly health post implementation. Monitoring and evaluation were conducted through observation and feedback discussions. The results demonstrated the successful establishment of the elderly health post structure, improved volunteer skills in vital sign assessment, and the implementation of the first elderly health post attended by 56 older adults. Volunteers showed increased practical skills and confidence in providing services, while community participation indicated positive acceptance of the program. Mentored establishment of an elderly health post through volunteer capacity strengthening supports the availability of sustainable community-based elderly health services.Abstrak: Peningkatan jumlah lansia menuntut tersedianya pelayanan kesehatan berbasis komunitas yang mampu melakukan pemantauan kesehatan secara promotif dan preventif. Wilayah mitra belum memiliki posyandu lansia serta kader belum memiliki keterampilan pemeriksaan kesehatan dasar sehingga pelayanan lansia belum optimal. Kegiatan pengabdian ini bertujuan memfasilitasi pembentukan posyandu lansia melalui penguatan kapasitas kader kesehatan. Metode pelaksanaan menggunakan pendekatan KKN dengan tahapan koordinasi, pembentukan struktur organisasi, pelatihan pemeriksaan kesehatan dasar, pelatihan senam lansia, serta pendampingan pelaksanaan posyandu lansia perdana. Hasil kegiatan menunjukkan terbentuknya struktur posyandu lansia, peningkatan kemampuan kader dalam melakukan pemeriksaan tanda vital, serta terselenggaranya posyandu lansia perdana dengan partisipasi 56 lansia. Kader menunjukkan peningkatan keterampilan praktis dan kepercayaan diri dalam pelayanan lansia, sementara masyarakat menunjukkan respons positif terhadap layanan yang terbentuk. Pendampingan pembentukan posyandu lansia melalui penguatan kapasitas kader terbukti mendukung tersedianya layanan kesehatan lansia berbasis masyarakat yang berpotensi berkelanjutan.